The evolution of the theory of poetic frenzy in Renaissance neoplatonism: The genius re-reading of Bruno’s «De gli eroici furori» (1585) - Pereira, Daniel Ortiz (Pensamiento. Revista de Investigación e Información Filosófica, 2021)
The Ficinian theory of the frenzies gave rise to one of the main debates within Neoplatonic philosophical currents of the 15th and 16th centuries, which rested upon the analysis of the nature, the functions and the attributes of the poet. This issue was especially significant to the coherent completion of two of the main elements of Ficino’s system: the theory of catharsis and the postulate of the immortality of the soul. This generated, as a consequence, an aesthetic paradigm concordant with the vertical condition of Neoplatonic anthropology, which, on the other hand, refused to create, strictly speaking, a subsequent theory of poetics. As Neoplatonic metaphysics were dispersed and transformed during the Late Renaissance, Giordano Bruno noticed, through a re-reading of the Ficinian texts on frenzy in his 1585 work De gli eroici furori, certain inconsistencies impossible to adapt to an emerging artistic and literary sensitivity, thus creating a new integral aesthetic model. The analysis of this evolution is to be the key point in this paper.